Matrix ill-condition analysis in spectrum recovery of DPCA HRWS SAR imaging - Ma, Changzheng (2021)
Conventional single-platform spaceborne synthetic aperture radar has a conflict between wide imaging swath width and fine-cross-range resolution. Displaced phase center antennas is one method to overcome this limitation. For spectrum recovery of nonuniform sampling, a detailed analysis on the relationship between coefficient matrix singularity and the number of effective phase centers (EPCs) passed by the platform during one pulse repetition time (PRT) is given. When the distance passed by the platform during one PRT is multiple of the distance between two EPCs plus a small value, the coefficient matrix is singularity. An explicit expression of the coefficient matrix is also derived.